Effects of noise exposure on young adults with normal audiograms II: Behavioral measures - Prendergast, Garreth; Millman, Rebecca E.; Guest, Hannah; Munro, Kevin J.; Kluk, Karolina; Dewey, Rebecca S.; Hall, Deborah A.; Heinz, Michael G.; Plack, Christopher J. (Elsevier, 2017)
An estimate of lifetime noise exposure was used as the primary predictor of performance on a range of behavioral tasks: frequency and intensity difference limens, amplitude modulation detection, interaural phase discrimination, the digit triplet speech test, the co-ordinate response speech measure, an auditory localization task, a musical consonance task and a subjective report of hearing ability. One hundred and thirty-eight participants (81 females) aged 18–36 years were tested, with a wide range of self-reported noise exposure. All had normal pure-tone audiograms up to 8 kHz. It was predicted that increased lifetime noise exposure, which we assume to be concordant with noise-induced cochlear synaptopathy, would elevate behavioral thresholds, in particular for stimuli with high levels in a high spectral region. However, the results showed little effect of noise exposure on performance. There were a number of weak relations with noise exposure across the test battery, although many of these were in the opposite direction to the predictions, and none were statistically significant after correction for multiple comparisons. There were also no strong correlations between electrophysiological measures of synaptopathy published previously and the behavioral measures reported here. Consistent with our previous electrophysiological results, the present results provide no evidence that noise exposure is related to significant perceptual deficits in young listeners with normal audiometric hearing. It is possible that the effects of noise-induced cochlear synaptopathy are only measurable in humans with extreme noise exposures, and that these effects always co-occur with a loss of audiometric sensitivity.